2020
DOI: 10.3390/electronics9122025
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stress Reduction of Power MOSFET with Dynamic Gate Voltage Control and Circulation Current Injection in Electric Drive Application

Abstract: While operating an electric drive under different load conditions, power switch devices experience thermal stress which provokes wear-out failures and compromises lifetime. In this paper, a model-based dynamic gate voltage control strategy is proposed to reduce the thermal stress by shaping the profile of conduction losses. Thermal stability criteria are investigated, which limit the gate voltage operating range; thus, current focalization and associated local heat up are avoided. After that, simulations and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Appl. 2023, 13, x FOR PEER REVIEW 3 of 10 mixed with their operation in the active region [19,[23][24][25][26]. Merging the non-conventional ON/OFF and linear control modes constitutes a technical novelty in the FFC-NMR field that led to a low power solution with a single-power semiconductor for a ferro-electromagnet.…”
Section: Operation Modes Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Appl. 2023, 13, x FOR PEER REVIEW 3 of 10 mixed with their operation in the active region [19,[23][24][25][26]. Merging the non-conventional ON/OFF and linear control modes constitutes a technical novelty in the FFC-NMR field that led to a low power solution with a single-power semiconductor for a ferro-electromagnet.…”
Section: Operation Modes Methodsmentioning
confidence: 99%
“…The optimized solution proposed in this work is hybrid and considers an ON/OFF operation of semiconductors The control solutions that will determine the operation of the semiconductors, S and S aux , must consider the dynamic nature of the magnet current. The optimized solution proposed in this work is hybrid and considers an ON/OFF operation of semiconductors mixed with their operation in the active region [19,[23][24][25][26]. Merging the non-conventional ON/OFF and linear control modes constitutes a technical novelty in the FFC-NMR field that led to a low power solution with a single-power semiconductor for a ferro-electromagnet.…”
mentioning
confidence: 99%
“…Moreover, it was shown that the proposed approach has impacts on conduction losses in case the switching transition exceeds a certain duration. In [193][194][195][196], Wang et al proposed an ATC method that can impact conduction losses by manipulating gate voltage and consequently drain-source resistance. However, in low gate voltage, the switch might get damaged because of a thermal runaway that can limit its applicability in a vast range of gate voltage.…”
mentioning
confidence: 99%